(untitled) (Czech Journal of Multidisciplinary Innovations, 2023)
In most cases, oil production occurs when it is replaced in the pore space of a productive formation with water or gas, both under natural operating conditions and with artificial methods of maintaining reservoir pressure by flooding or gas injection.